Magnetic Resonance Cholangiopancreatography in the Diagnosis of Haemobilia - Ines Casazza; Mara Angela Guglietta; Giuseppe Argento (Case Reports in Radiology)
Haemobilia is a rare cause of unrecognized gastrointestinal bleeding and is hard to diagnose. Through the present case report we aim to corroborate magnetic resonance relevance in the evaluation of biliary system and bile features, investigating on its role in patients with acute biliary diseases. We report a case of a Caucasian 48-year-old man who was admitted due to abdominal pain and fever. After an ultrasonography exam we detected multiple cysts in the hepatic left lobe: imaging features, laboratory findings, and patient past work experience (woodcutter) suggested a diagnosis of hepatic Echinococcosis. Once surgery decision was taken, patient underwent an intervention of cystopericystectomy. On the 8th postoperative day, the procedure was complicated by black stool, jaundice, and severe anaemia. Acomputed tomography revealed an inhomogeneous collection with some air bubbles in the area of previous surgical intervention, but it was not able to solve the diagnosis question. At this stage a magnetic resonance study was mandatory. On T2-weighted images we observed an expanse gallbladder with hypointense intraluminal material and a considerable intrahepatic biliary system dilatation due to bloody material. On the basis of these examination results, we supposed haemobilia arising from previous surgical intervention. A therapeutic endoscopic retrograde cholangiopancreatography procedure led to decompression of biliary system through a major papilla sphincterotomy with spillage of bile mixed with blood clots.